COMBINATION OF GENRES IN PAINTING - Batir Baratboyev Mamajanovich; Sharaboyev Ulugbek Muhammedovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
This article provides a brief history of the art of painting, the genres of painting, the introduction of the still life genre, and the sequence and rules of working with the still life genre in painting